Bioactivity and antibacterial activity against E-coli of calcium-phosphate-based glasses: Effect of silver content and crystallinity. Issue 16 (November 2017) - Capela, M.N.; Tobaldi, D.M.; Oliveira, C.; Pereira, A.; Duarte, A.S.; Seabra, M.P.; Fernandes, M.H.V.
Abstract: In this work we developed improved bioactive glasses and glass-ceramics for biomedical applications, investigating their in vitro bioactivity, biocompatibility and antibacterial properties against E-Coli . A melt-quenched bioactive glass of the SiO2 -CaO-P2 O5 -MgO system was modified with the addition of 1 and 2 mol% Ag2 O and the 1 mol% Ag2 O-containing glasses were then heat treated to produce glass-ceramics. Surface modifications after soaking in SBF and ionic concentration changes showed that addition of silver and crystallization did not affect bioactivity although crystalline phases promoted a decrease in the degradation rate. Biocompatibility of all Ag-containing glasses and glass-ceramics was confirmed for certain samples concentrations. The antibacterial activity of the glasses against E-Coli was generally improved with decreasing particle size or increasing Ag2 O. The Ag-containing glass-ceramics with higher content of crystalline phase appears as a promising biocompatible biocidal material with potential applications in bone-related diseases.